Can the Anterolateral Ligament Be Reliably Identified in Anterior Cruciate Ligament–Intact and Anterior Cruciate Ligament–Injured Knees on 3-T Magnetic Resonance Imaging? - Marshall, Tyler (Orthop J Sports Med, 2018)
BACKGROUND: The anterolateral ligament (ALL) has been described as an extracapsular stabilizer of knee rotational stability. Investigators have shown a renewed interest in the ALL and further evaluated its anatomy and biomechanical role as a knee stabilizer. The appearance of the ALL on magnetic resonance imaging (MRI) remains inconsistent across the literature. PURPOSE: The aims of this study were 2-fold. The first objective was to further investigate the appearance of the uninjured ALL on MRI and provide data regarding interrater agreement in identifying the ligament. The second objective was to describe the incidence of concomitant ALL injuries in anterior cruciate ligament (ACL)–injured knees and provide data regarding interrater agreement in identifying and grading these injuries. STUDY DESIGN: Cohort study (diagnosis); Level of evidence, 3. METHODS: Fifty consecutive MRI scans of non–ACL-injured knees (control) and 50 consecutive MRI scans of ACL-injured knees performed at a single sports medicine center were identified. Three musculoskeletal radiologists independently reviewed the MRI scans in a randomized and blinded fashion. In the control group, the reviewers classified the ALL as visualized or not and did so for the proximal, middle, and distal thirds of the ligament. In the ACL tear group, the reviewers classified the ALL as visualized or not for each third of the ligament. They noted whether the ligament was injured and graded the injury as low, intermediate, or high. RESULTS: All 3 segments of the ALL were visualized in a mean 11% of patients. The ALL was partially visualized in a mean 68% of patients. The distal third of the ALL was injured 28% (14/50) of the time in the ACL tear group. The agreement rate among raters for classifying the injury status was fair to poor. CONCLUSION: Visualization of the ALL was inconsistent in the current study. Identifying and grading an injury to the ALL were difficult and had poor interobserver agreement. Using MRI to aid in the diagnosis of an ALL injury in the setting of an ACL tear is unreliable according to our study results. Further research looking at consistent ALL identification and injury patterns should be undertaken.